Tradisi Intelektual Fardhu Ain dan Fardhu Kifayah Pesantren dalam Menanggulangi Terorisme - Taqiyuddin, Muhammad (Jurnal Penelitian Pendidikan Islam, 2021)
Most people believe that religion and ideology contribute to the spread of terrorism. Thus, it can be seen from the method of text interpretation and the implementation of over-textual and rigid interpretations in religious studies that are very instant and indoctrinal; which resulted in the spread of 'radicalism'. This aspect forgets the essence of Islamic education which emphasizes tolerance, courtesy, and love for peace. Conversely, Islamic studies that are too contextual, will eliminate the epistemological footing; that is, their identity and essence, because they merely follow all the social changes that continue to occur without regard to the wisdom and wisdom of local wisdom. Thus, the search for knowledge is no longer sacred and then encourages the loss of etiquette (loss of adab). Therefore, conceptual efforts in Islamic education need to be carried out appropriately. This qualitative model study seeks to collect fragments and data from various studies based on Islamic turots on the fardhu ‘ain and fardhu kifayah models and their relevance in various contexts of Islamic studies such as integrative aspects between religious science and social science and contemporary technology. Through content analysis, thematic analysis as well as critical discourse analysis. This study concludes that the scientific equilibrium based on fardhu ‘ain and fardhu kifayah has proven to make Islamic insights and discourse broad and flexible, so as to give birth to attitudes that both physically and spiritually represent the essence of Islamic teachings themselves.